Legal Protection for Victims of Fraudulent Investment Crimes Based on Restorative Justice at the Salatiga Police Resort - Rifo, Kana; Maerani, Ira Alia (UNISSULA Semarang, 2025)
This study aims to determine and obtain data regarding legal protection for victims of fraudulent investment crimes using a restorative justice approach, then the obstacles faced by the police in handling this case and how to resolve this case using a restorative justice approach. The juridical-sociological research method is an approach in legal research that combines legal (juridical) and social (sociological) aspects to understand how law interacts with society and its impact on social order. This method involves collecting qualitative data, such as interviews, observations, and document analysis, to describe and explain how law affects society, how society responds to law, and how this interaction can shape better legal policies using the theory of restorative justice and the theory of law enforcement in an Islamic perspective. The results of the study show that First, legal protection based on restorative justice for victims of fraudulent investment crimes such as the fulfillment of victim rights, counseling, medical services or assistance, legal assistance, and providing information to victims related to the investigation and examination process of the crime experienced by the victim. Second, the obstacles faced in resolving the case are that the victim asks for the case to continue, there are parties who provoke, and want to provide a deterrent effect on the perpetrator. Third, the process of resolving criminal cases in Indonesia can usually be resolved through litigation or trials. However, the idea of resolving criminal cases using non-litigation methods or can also be called restorative justice emerged. Restorative justice or restorative justice contains the meaning of a restoration of relationships and atonement for mistakes that the perpetrator wants to make to the victim using methods outside the court with the aim that the problem can be resolved properly and an agreement is reached between the parties. By looking at it from the perspective of the perpetrator, victim and case.